2021
DOI: 10.3389/fbioe.2021.787020
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of an Ex Vivo Inflammatory Osteoarthritis Model With Human Osteochondral Explants

Abstract: Osteoarthritis (OA) is the most common degenerative joint disease without clear pathophysiological mechanism and effective drugs for treatment. Although various animal models exist, the translation of the outcome into clinics remains difficult due to species differences. In this study, an ex vivo inflammatory OA model was induced using different concentrations of interleukin one beta (IL-1β) and tumor necrosis factor α (TNF-α) on explants from the human femoral head. In the inflammatory OA groups, the gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 34 publications
0
0
0
Order By: Relevance
“…A previous study demonstrated that the addition of in ammatory cytokines IL-1β and TNF-α for 7 days to human osteochondral plugs could induce osteoarthritic characteristics ex vivo [19]. Human cartilage is a superior model for investigating the response of cartilage in joint diseases compared to bovine cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that the addition of in ammatory cytokines IL-1β and TNF-α for 7 days to human osteochondral plugs could induce osteoarthritic characteristics ex vivo [19]. Human cartilage is a superior model for investigating the response of cartilage in joint diseases compared to bovine cartilage.…”
Section: Discussionmentioning
confidence: 99%